In his father's footsteps : a novel - Steel, Danielle (Delacorte Press, 2018)
When U.S. troops occupy Germany, friends Jakob and Emmanuelle are saved from the terrible fate of so many in the camps. With the help of sponsors, they make their way to New York. In order not to be separated, they allow their friendship to blossom into love and marriage, and start a new life on the Lower East Side, working at grueling, poorly paid jobs. Decades later, through talent, faith, fortune, and relentless hard work, Jakob has achieved success in the diamond business, invested in real estate in New York, and shown his son, Max, that America is truly the land of opportunity. Max is a rising star, a graduate of Harvard with friends among the wealthiest, most ambitious families in the world. And while his parents were thrown together by chance, Max chooses a perfect bride to start the perfect American family. An opulent society wedding. A honeymoon in Tahiti. A palatial home in Greenwich. Max<U+2019>s lavish lifestyle is unimaginable to his cautious old-world father and mother. Max wants to follow his father<U+2019>s example and make his own fortune. But after the birth of children, and with a failing marriage, he can no longer deny that his wife is not the woman he thought she was. Angry and afraid, Max must do what he has never done before: struggle, persevere, and learn what it means to truly walk in his father<U+2019>s footsteps, while pursuing his own ideals and setting an example for his children.